2014
DOI: 10.1007/s10517-014-2411-6
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Effects on Serum Cytokine Profiles of Rats with Different Behavioral Parameters in Acute Emotional Stress

Abstract: The effects of melatonin (epiphyseal neurohormone) on the serum cytokine profiles of rats with different behavioral characteristics were studied after acute emotional stress. One-hour immobilization of animals with simultaneous electrocutaneous stimulation of subthreshold intensity served as the stress model. Acute stress exposure of animals with active behavior led to reduction of the peripheral blood concentrations of pro-inflammatory (IL-1α, IL-1β, IL-2, IFN-γ, granulomonocytic CSF) and anti-inflammatory (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…These conditions include physical and psychological stressful events like exercise, exposure to extreme thermal conditions, different kinds of pain, depression, sleep deprivation, hypoxia, etc. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In general, an increased IL-10 level during these events is associated with better outcome and adaptation.…”
Section: Physiological and Nonimmune Conditionsmentioning
confidence: 99%
“…These conditions include physical and psychological stressful events like exercise, exposure to extreme thermal conditions, different kinds of pain, depression, sleep deprivation, hypoxia, etc. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In general, an increased IL-10 level during these events is associated with better outcome and adaptation.…”
Section: Physiological and Nonimmune Conditionsmentioning
confidence: 99%
“…We speculated that it was the high levels of serum proinflammatory cytokines which suppressed autophagy activity of PBMCs obtained from LPS-challenged transgenic animals. It has been reported that proinflammatory cytokines suppress autophagy activity [96][97][98] and several reports also report that melatonin elevates serum levels of some proinflammatory cytokines [99,100]. However, the exact mechanisms are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the role of IFN-γ in depression, conflicting results were reported. Although several studies demonstrated that CMS could result in a significant increase of IFN-γ in both the brain and periphery, it was also reported that either acute or chronic stress exposure would lead to a significant suppression of IFN-γ production [28][29][30][31]. These contrasting observations might be the result of the intertwined neuro-immune system.…”
Section: Discussionmentioning
confidence: 99%